2021
DOI: 10.1088/1475-7516/2021/10/020
|View full text |Cite
|
Sign up to set email alerts
|

The effect of kick velocities on the spatial distribution of millisecond pulsars and implications for the Galactic center excess

Abstract: Recently it has become apparent that the Galactic center excess (GCE) is spatially correlated with the stellar distribution in the Galactic bulge. This has given extra motivation for the unresolved population of millisecond pulsars (MSPs) explanation for the GCE. However, in the "recycling" channel the neutron star forms from a core collapse supernovae that undergoes a random "kick" due to the asymmetry of the explosion. This would imply a smoothing out of the spatial distribution of the MSPs. We use N -body s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Furthermore, if the GCE is due to millisecond pulsars (MSPs), the spatial morphology of the signal could reveal the formation mechanisms of the MSPs. Assuming the primordial formation scenario for MSPs in the GC, studies [16,17] have implemented state-of-the-art population synthesis codes to build synthetic populations of MSPs. The picture that is emerging from such efforts is that the MSPs responsible for the GCE should (approximately) trace the distribution of old stars in the Galactic bulge-a composite structure made up of a triaxial barlike structure extending a few kiloparsecs and a concentrated nuclear component in the inner ∼ 200 pc of GC.…”
Section: Understanding the Spatial Morphology Of The Gcementioning
confidence: 99%
“…Furthermore, if the GCE is due to millisecond pulsars (MSPs), the spatial morphology of the signal could reveal the formation mechanisms of the MSPs. Assuming the primordial formation scenario for MSPs in the GC, studies [16,17] have implemented state-of-the-art population synthesis codes to build synthetic populations of MSPs. The picture that is emerging from such efforts is that the MSPs responsible for the GCE should (approximately) trace the distribution of old stars in the Galactic bulge-a composite structure made up of a triaxial barlike structure extending a few kiloparsecs and a concentrated nuclear component in the inner ∼ 200 pc of GC.…”
Section: Understanding the Spatial Morphology Of The Gcementioning
confidence: 99%
“…This GC excess (GCE) might be explained by the emission of GeV-scale dark matter particles (e.g., [1,4,[7][8][9][10][11]) or by a new population of millisecond pulsars [4,6,12,13]. Although the predicted spectrum of either of these hypothetical sources is degenerate, their spatial morphologies are expected to be quite different [14]. Recent studies [15][16][17][18][19][20] demonstrated that there is a correlation 1 between the spatial morphology of the GCE and that of Galactic bulge stars in the Galactic center.…”
Section: Introductionmentioning
confidence: 99%
“…This GC excess (GCE) could in principle be explained by the self-annihilation of GeV-scale dark matter particles (e.g., [1,4,[7][8][9][10][11]) or by a large population of gamma-ray emitting pulsars [4,6,12,13]. While the predicted spectrum for either of these two hypothetical sources is degenerate, their spatial morphologies are expected to be quite different [14]. Interestingly, a string of recent articles [15][16][17][18][19][20] have found a correlation 1 between the spatial morphology of the GCE and that of stellar mass in the Galactic bulge.…”
Section: Introductionmentioning
confidence: 99%